Guanaco hunting strategies in the northern plains of Tierra del Fuego, Argentina - Santiago, Fernando Carlos (2016)
This article analyses the access to animal resources during the Holocene using the evidence from a key site – Las Vueltas 1, LV1–, localized in the Northern steppe of Tierra del Fuego (Argentina). The contexts analysed from this site yielded at least 85 individuals of Lama guanicoe (guanaco) based on MNI counts: 41 on surface level, 37 in the 3rd occupation, 6 in the 2nd, and just 1 in the 1st. LV1 occupies a low aeolian dune between two lagoons bordered by Tertiary sandstone outcrops; it was interpreted as an appropriate space to capture, kill and process guanacos from the beginning of the Late Holocene. The most useful way to use this natural trap was to work in a communal strategy, implying the participation of several hunters. Furthermore, the site could have also been used for the capture of a single animal, or a reduced number of animals, as happened in the 2nd occupation. As far as the context of the 3rd occupation is concerned, it is proposed that this communal strategy may have been used at a larger scale, turning the site into a communal hunting area that we interpret as a “mass kill“ site. This hypothesis was supported by evidence such as the large amount of guanaco bone remains, the limited and specific range of the fauna assembled at the place, the catastrophic death pattern, the sex and age of hunted animals, a topography appropriate to ambush animals and the large number of fractured lithic points (when compared with other Fuegian sites). Certain conditions such as the topographic relief, hunting season, animal behaviour, social or political issues would have led hunter-gatherers to practice this kind of communal and mass hunting.